2008
DOI: 10.1111/j.1744-618x.2008.00089.x
|View full text |Cite
|
Sign up to set email alerts
|

A Validation Study of the Nursing Diagnosis Anxiety in Brazil

Abstract: The adequate preparation of undergraduate and postgraduate nurses in nursing diagnosis is important in improving the quality of care given to patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 11 publications
0
9
0
3
Order By: Relevance
“…Using the scoping question: "Which studies present validation of nursing diagnoses in adults?" we obtained, after limiting search results to English and Czech texts for the publication period of 1/2000-12/2018 and after eliminating duplicate and irrelevant texts, the following eight relevant studies with content validation of NANDA International diagnoses: Oliveira, Chianca, Rassool (2008), Zeleníková et al (2011), Vaněčková, Sollár, Vörösová (2012), Zeleníková, Žiaková (2012), Vörösová et al (2012), Zeleníková et al (2014), Pompeo, Rossi, Paiva (2014) and Santos, Almeida and Lucena (2016). It is worth pointing out that all the authors come from one of three countries: Brazil, the Czech Republic and Slovakia.…”
Section: Discussionmentioning
confidence: 99%
“…Using the scoping question: "Which studies present validation of nursing diagnoses in adults?" we obtained, after limiting search results to English and Czech texts for the publication period of 1/2000-12/2018 and after eliminating duplicate and irrelevant texts, the following eight relevant studies with content validation of NANDA International diagnoses: Oliveira, Chianca, Rassool (2008), Zeleníková et al (2011), Vaněčková, Sollár, Vörösová (2012), Zeleníková, Žiaková (2012), Vörösová et al (2012), Zeleníková et al (2014), Pompeo, Rossi, Paiva (2014) and Santos, Almeida and Lucena (2016). It is worth pointing out that all the authors come from one of three countries: Brazil, the Czech Republic and Slovakia.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies of content validation showed higher, similar or lower number of experts when compared to the number of experts in this search: 120 nurses (nursing diagnosis of anxiety) (11) , 72 experts (nursing diagnosis of spiritual anguish) (12) (13) , 58 experts (nursing diagnosis of nausea) (14) , 50 experts (diagnosis of deficient knowledge) (4) , 32 experts (diagnostic of sexual dysfunction and ineffective sexuality pattern) (15) , 16 experts (diagnostic of fear and anxiety) (16) , 21 experts (nursing interventions for patients with diabetes mellitus) (17) .…”
Section: Discussionmentioning
confidence: 99%
“…Substance abuse [27][28][29][30] ; Low selfesteem; 1,19,[31][32][33] Previous hospitalizations; 34,35 Loneliness; 30 Heredity; 36 Family history of anxiety; 27,31,37 Previous history of anxiety. 36,[38][39][40][41][42] Unknown environment 1,18,34,35 ; Threat to the current condition; 18,43 Poor knowledge; 19,41 Stressors; 1,18,28,38,39,42,44,45 Death threat; 46 Uncertainty 41,42 ; Support system separation; 19,34,38,47 Young age; 27,37,40,41,[48][49][50] Female gender; 27,…”
Section: Anxiety Anxiety and Fear Fear Antecedentsmentioning
confidence: 99%